Perfectionism, Health, and Well-Being 2015
DOI: 10.1007/978-3-319-18582-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizations of Perfectionism, Health, and Well-Being: An Introductory Overview

Abstract: Perfectionism research has burgeoned over the past two decades. During this time, there have been a number of empirical and theoretical advances providing insight into the nature of perfectionism and its associated risks. Broadly, perfectionism can be described as setting and striving for excessively high and often unrealistic standards, accompanied by frequent thoughts focused on attainment of these standards and overly critical self-evaluation (Frost, Marten, Lahart, & Rosenblate, 1990). However, it is now r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 76 publications
3
41
0
1
Order By: Relevance
“…Results demonstrated that the adaptive group of students had a higher level of well-being than maladaptive and Non-Perfectionist and the difference were statistically significant. This finding is consistent with the results of research (Bulina, 2014;Flett & Hewitt, 2006;Kenny & Hicks, 2014), and Sirois and Molnar (2016), but this result is inconsistent with Grzegorek et al (2004) and Rice and Ashby (2007) studies. In explaining this finding, it can be said that perfectionism is a construct that we all experience in different degrees (Egan et al, 2014), thus each of the different levels of perfectionism will have different effects on psychological well-being and individual performance and have influence in all life aspects (Stoeber et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Results demonstrated that the adaptive group of students had a higher level of well-being than maladaptive and Non-Perfectionist and the difference were statistically significant. This finding is consistent with the results of research (Bulina, 2014;Flett & Hewitt, 2006;Kenny & Hicks, 2014), and Sirois and Molnar (2016), but this result is inconsistent with Grzegorek et al (2004) and Rice and Ashby (2007) studies. In explaining this finding, it can be said that perfectionism is a construct that we all experience in different degrees (Egan et al, 2014), thus each of the different levels of perfectionism will have different effects on psychological well-being and individual performance and have influence in all life aspects (Stoeber et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, recent research has suggested that perfectionism includes both positive and negative qualities (Chufar & Pettijohn, 2013). Also, studies show that perfectionism involves an adaptive component that improves psychological well-being (Flett & Hewitt, 2006;Sirois & Molnar, 2016;Stoeber & Otto, 2006). The study of the second hypothesis showed that university students with adaptive perfectionism had higher mean scores in the sub-scales of psychological well-being, autonomy, purpose in life, positive relations with others, and environmental mastery than those with maladaptive and nonperfectionist students, and this difference was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now widely accepted that both dimensions of perfectionism previously identified in factor analysis (e.g., Bieling, Israeli, & Antony, 2004), perfectionistic strivings and perfectionistic concerns, are risk factors for psychopathology (Shafran, Cooper, & Fairburn, 2002;Flett & Hewitt, 2014;Gaudreau, 2018;Blasberg, Hewitt, Flett, Sherry, & Chen, 2016;Limburg, Watson, Hagger, & Egan, 2017). Perfectionistic strivings involve seeking to attain relentlessly demanding, extremely high, and often unrealistic standards for the self (Sirois & Molnar, 2016). Perfectionistic concerns involve being excessively preoccupied with others' expectations and evaluations, excessively self-critical, and unable to be satisfied with one's successes (Sirois & Molnar, 2016).…”
mentioning
confidence: 99%